Killer whale attacking on South American sea lion associated to a fishing vessel: predator and prey tactics - Grandi, Maria Florencia; Loizaga de Castro, Rocio; Crespo, Enrique Alberto
Interactions between killer whales and sea lions are widely known. This work describes the predator-prey behaviour of killer whales and South American sea lion associated to a trawling fishery. Particularly in Argentina the predatory behaviours of killer whales and anti-predatory behaviours of South American sea lions were described from land-based observations from coast, but predator-prey behaviour of these species is poorly known from open waters. Here we account of a killer whale group attacking on an individual sea lion, of a video recorded from a trawling vessel, along with an interview of the ship captain. This predator-prey behaviour represents an example on the complexity of interactions between marine mammals and fisheries along Patagonia coast. Las interacciones entre orcas y lobos marinos son ampliamente conocidas. Este trabajo describe el comportamiento predador-presa entre orcas y un lobo marino sudamericano asociados a un barco pesquero de arrastre. Particularmente en Argentina el comportamiento predatorio de las orcas y el anti-predatorio de los lobos marinos comunes fueron descriptos mediante observaciones costeras, pero se sabe poco sobre el comportamiento de estas especies en aguas abiertas. En este trabajo, a partir de un video grabado desde un barco de pesca arrastrero, junto con la entrevista del capitán del barco, se describe cómo un grupo de orcas ataca a un lobo marino Sudamericano. Este comportamiento predador-presa representa un ejemplo sobre la complejidad de las interacciones entre mamíferos marinos y las pesquerías a lo largo de la costa patagónica. Fil: Grandi, Maria Florencia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Loizaga de Castro, Rocio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Crespo, Enrique Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Universidad Nacional de la Patagonia. Facultad ...